Asking for truffle : a Southern Chocolate Shop mystery - St. James, Dorothy (St. James, Dorothy. Southern Chocolate Shop mysteries, 2017)
Chocoholic Charity Penn must save her new seaside chocolate shop from a deadly assortment of threats in this sweet series debut. When Charity Penn receives a letter saying she won a trip to South Carolina for free confectionery lessons at a seaside chocolate shop, the Chocolate Box, she's skeptical: she knows that she never entered the contest. An old prep school friend offers to look into the phony prize - and ends up drowned in a vat of chocolate. A guilt-stricken Penn heads to the sunny Southern beach town to investigate. Though she's wary of the locals, their eccentric vibe makes her defenses melt away. But learning the art of crafting delicious chocolates turns bittersweet when she unwraps a dark and deadly plot to destroy the charming resort town. Only Penn's quick thinking and a mysterious cask of rare cocoa beans can save the town she's learned to love.